Young People's Perspectives on End-of-Life : Death, Culture and the Everyday - Coombs, Sarah (Studies in Childhood and Youth, 2017)
This book challenges adult assumptions that young-people do not, cannot and should not think about death. The author uses everyday material objects in order to facilitate a range of conversations, revealing lively engagement with the topic. Cultural resources, such as literature and film, provide a rich variety of perspectives on and responses to death, whilst equally providing an opportunity to challenge many of these representations as unreal and unauthentic. The book contains personal narratives of loss and memories of loved ones, presenting a variety of encounters with significant deaths, the stories being told in an array of vibrant, amusing and emotive ways. Similarly, death is explored from a variety of religious and scientific frameworks, highlighting rich and changing perspectives. Such shifting and exciting vistas are a largely undiscovered part of young-people's lives and situate them in a landscape not often associated with childhood. Young-People's Perspectives on End-of-Life will be of interest to students and scholars across a range of disciplines, including Childhood and Youth Studies, Death Studies, Qualitative Research Methodologies, Sociology, Anthropology and Education. .